2016
DOI: 10.3390/nu8060337
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Folic Acid Supplementation in Autistic Children Participating in Structured Teaching: An Open-Label Trial

Abstract: Autism spectrum disorders (ASD) are recognized as a major public health issue. Here, we evaluated the effects of folic acid intervention on methylation cycles and oxidative stress in autistic children enrolled in structured teaching. Sixty-six autistic children enrolled in this open-label trial and participated in three months of structured teaching. Forty-four children were treated with 400 μg folic acid (two times/daily) for a period of three months during their structured teaching (intervention group), whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 44 publications
2
34
0
1
Order By: Relevance
“…Numerous studies have reported that dysfunctional folate-methionine pathway enzymes may play an important role in the pathophysiology of autism [5]. In such children, a three-month folic acid supplementation has been shown to improve autistic features, particularly cognition and communication [6], as was the case in our patient. We undertook rapid evaluation, with early intervention, and evaluated our patient's response using CARS, which is a 15-point behavioral rating scale developed to both identify autism as well as define the severity of the disorder [7].…”
Section: Discussionsupporting
confidence: 78%
“…Numerous studies have reported that dysfunctional folate-methionine pathway enzymes may play an important role in the pathophysiology of autism [5]. In such children, a three-month folic acid supplementation has been shown to improve autistic features, particularly cognition and communication [6], as was the case in our patient. We undertook rapid evaluation, with early intervention, and evaluated our patient's response using CARS, which is a 15-point behavioral rating scale developed to both identify autism as well as define the severity of the disorder [7].…”
Section: Discussionsupporting
confidence: 78%
“…As for neurodegenerative diseases, one hypothesis of the significance of HHcy in the etiology of ASD is that Hcy is a powerful excitotoxin, and its metabolic products can cause damage in some proteins, generating "abnormal toxin proteins" and inducing an autoimmune response [125]. Some studies on the neurotoxicity of Hcy have demonstrated that Hcy can induce neuronal damage, causing activation of N-methyl-d-aspartate (NMDA) receptors and cell loss through excitotoxicity as well as apoptosis [124][125][126][127][128][129][130][131]. Additionally, Fulceri et al [127] observed that autistic children often have gastrointestinal disorders and/or are picky eaters, and these factors could lead to an inadequate dietary intake, altered nutrient absorption, and micronutrient deficiency, particularly vitamin B deficiency, which causes increased plasma Hcy levels and worsening of autism.…”
Section: Hhcy and Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…On the basis of the relationship between low folate levels, HHcy, and autism, Sun et al [131] in an intervention study demonstrated that supplementation with 800 µg/day of folic acid in children (mean age 52.00 ± 13.13 months) improved autism symptoms related to receptive language, cognitive verbal/preverbal, sociability, affective expression, and communication, and that this treatment also improved the concentration of folic acid, reduced Hcy plasma levels, and normalized glutathione redox metabolism. These results, according to Józefczuck et al [132], suggest serum Hcy levels as a useful biomarker for diagnosis of autism spectrum disorder in children as well as for the efficacy of treatment.…”
Section: Hhcy and Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…The pathway of cysteine and methionine cycle, folate(vitamin B9) metabolism, and Hcy transsulfuration are interrelated and constitute the folate-related metabolism together [27]. The folate-related pathway has a critical role in cell proliferation, DNA synthesis, immune function, and neural development [28]. Vitamin B6 and B12 are cofactors of these biological processes.…”
Section: Discussionmentioning
confidence: 99%